The Use of English Subtitle on Films to Help Self-Study in Mastering Vocabulary - Nurfauziah, Dwi Hana; Aflahah, Noor Aida; Riskina, Aulia; Dayanti, Gista Rahma; Yansyah, Yansyah; Kurniawan, Dani; Dharojah, Rakhma Widya (Universitas Muhammadiyah Surakarta, 2023)
The master key to understanding the meaning of foreign language sentences is vocabulary. Mastering a lot of vocabulary makes it easier to understand the reading, follow a conversation, give an answer, and speak a foreign language. Without a proper vocabulary, the students cannot communicate and understand what is being communicated. The goal of vocabulary teaching should be to get students to actively think about the meaning of words and how we can use them in different situations. The use of subtitles in films is an effective way to make it easier for students to develop an understanding of the sentences and vocabulary conveyed in films. For students studying English, movie subtitles have a distinct appeal, especially for expanding vocabulary. The purpose of this study is to see how the use of subtitles in films is beneficial for mastering students' vocabulary and find out whether subtitles in films can influence students' mastery of English vocabulary. The research method used by the author is a qualitative descriptive research. Data collection was carried out through documentation and interviews with research subjects. The subjects of this research were two students majoring in English class of 2020 at a private campus in South Kalimantan. This study finds the conclusion that the use of films with English subtitles as a strategy for teaching vocabulary independently can help students to master English vocabulary in a fun and interesting way because students enjoy and are motivated to learn vocabulary.